Epitopes of streptococcal M proteins shared with cardiac myosin (The Rockefeller University Press, 1985)
We present evidence that M proteins from three different serotypes of group A streptococci share epitopes with cardiac myosin. Rabbit antisera evoked by a purified fragment of type 5 M protein crossreacted with myosin, but not alpha-tropomyosin, actin, or myosin light chains. In enzyme-linked immunosorbent assays, the myosin-crossreactive antibodies were totally inhibited by type 5 M protein and partially inhibited by types 6 and 19 M proteins. The affinity-purified myosin antibodies opsonized type 5 streptococci, indicating that they were directed against protective M protein epitopes on the surface of the organisms. Immunoblot analyses demonstrated the binding of the crossreactive antibodies to myosin heavy chains. Sera from patients with acute rheumatic fever showed significantly stronger reactions with myosin than did sera from their siblings, hospitalized controls, or patients with poststreptococcal glomerulonephritis.